Bismuth single atom supported CeO2 nanosheets for oxidation resistant photothermal reverse water gas shift reaction. Issue 18 (12th August 2022) - Kang, Xiaoxiao; Yuan, Dachao; Yi, Zhiqi; Yu, Chenyang; Yuan, Xiaoxian; Liang, Baolai; San, Xingyuan; Gao, Linjie; Wang, Shufang; Li, Yaguang
Abstract : Bi single atoms supported on CeO2 nanosheets combined with a Ti2 O3 based photothermal device showed oxidation resistance and outperforming weak solar driven RWGS with a CO production rate of 31.00 mmol g −1 h −1 under 3 sun units of irradiation. Abstract : Photothermal reverse water gas shift reaction (RWGS) is one of the most essential green technologies for CO2 utilization. However, the intermittent photothermal RWGS makes all catalysts inactive due to air oxidation. Therefore, investigating new catalysts with high activity and oxidation resistance simultaneously is imperative for the industrialization of photothermal RWGS, which has not yet been realized. Here, Bi single atoms supported by CeO2 nanosheets are synthesized via the soft template method, which showed high activity and stability for RWGS under air corrosion at 400 °C, revealing unprecedented oxidation resistance. Experiments and first principles calculation confirm that the Bi single atoms kept their +3 valence state during RWGS and have a low energy barrier for RWGS, thus leading to high activity and oxidation resistance for RWGS. When loading BiO x /CeO2 in a Ti2 O3 based photothermal system, a CO generation rate of 31.00 mmol g −1 h −1 was achieved under 3 sun units of irradiation, 4 times higher than the state of the art of solar driven RWGS under 20 sun units of irradiation. Moreover, there is still no inactivation of BiO x /CeO2 in intermittent air oxidation, which can directly promote the industrialization of photothermal RWGS.